The Qur’an Education Activities at the Qur’an House Bustanul Qira'ah Indonesia - Erlina Erlina; Ranggi Pranata; Rayhan Feyza Alfarikh; Rina Aulia Rahman; Zulkhrufil Shadri (International Journal of Multidisciplinary Research of Higher Education, 2022)
This study aims to explore how the educational model of the art of reading the Qur’an is for students at the Qur’an bustanul qira'ah Islamic boarding school. This research used a qualitative method with a phenomenology approach, the research data was taken through direct interviews with ten informants (boarding school administrators, boarding school teachers, village government, students, and parents of students), to strengthen the interview data the author made observations for two months. By being directly involved in the activities of the bustanul qira'ah Qur’an boarding school. All interview and observation data were then analyzed thematically using the Nvivo 12 software. Overall the results of the analysis showed that there were three Qur’an educational activities in the bustanul qira'ah Islamic boarding school. The three activities are: i) learning the art of recitation (using the rhythms of bayyati, nahawand, and rast), ii) learning the art of tartil (with the rhythms of bayyati from thoha al junayd, and nahawand from sheikh Misyari rasyid), iii) memorizing the Qur’an. The results of this study can be used as initial data for future researchers in examining different issues related to this problem and various other issues that are relevant to this context.